Influence of damage and structural periodicity on the electromechanical impedance for SHM - Dias, Lorena Lopes [UNESP]; Gonsalez-Bueno, Camila Gianini [UNESP]; Bueno, Douglas Domingues [UNESP] (ABCM, 2025)
Structural Health Monitoring (SHM) is the engineering area dedicated to analyzing structural conditions, in order to detect damage using various monitoring and data analysis methods. In particular, the Electromechanical Impedance (EMI) technique stands out for its remarkable ability to detect incipient damage using non-intrusive piezoelectric transducers (PZTs). Traditionally, research in this area has relied heavily on experimental data, often limiting the understanding of this technique to specific testing conditions. However, recent efforts have shifted towards expanding knowledge of EMI through numerical-computational simulations. In this context, the present work aims to enhance an EMI model by incorporating the effects of damage and periodic structure, moving beyond the baseline configuration considered in the reference analytical model, used as a starting point. Symmetric damage was simulated in an Euler-Bernoulli beam comprising three unit cells and two homogeneous regions, with PZTs symmetrically coupled to one. Damage was examined in two dynamic contexts: flexural and longitudinal vibrations. The findings indicate that flexural dynamics exhibit heightened sensitivity to damage detection, primarily due to the higher amplitude and density of peaks across the frequency range. This study provides a deeper understanding of the technique’s ability to detect damage in more complex scenarios and extends the model’s applications.

O Monitoramento da Integridade Estrutural (SHM, do inglêsStructural Health Monitoring ) é a área da engenharia dedicada à análise das condições estruturais, com o objetivo de detetar danos utilizando vários métodos de monitoramento e análise de dados. Em particular, a técnica de Impedância Eletromecânica (EMI, do inglês Electromechanical Impedance) destaca-se pela sua notável capacidade de detectar danos incipientes utilizando transdutores piezoelétricos não intrusivos (PZTs). Tradicionalmente, a pesquisa nessa área tem se baseado fortemente em dados experimentais, muitas vezes limitando a compreensão dessa técnica a condições específicas de cada de teste. No entanto, esforços recentes têm se voltado para a expansão do conhecimento sobre a EMI por meio de simulações numéricas-computacionais. Nesse contexto, o presente trabalho visa aprimorar um modelo EMI ao incorporar os efeitos de danos e periodicidade, indo além da configuração básica considerada no modelo analítico de referência, usado como ponto de partida. O dano simétrico foi simulado em uma viga Euler-Bernoulli composta por três células unitárias e duas regiões homogêneas, com PZTs acoplados simetricamente a uma delas. O dano foi examinado em dois contextos dinâmicos diferentes: vibrações flexurais e longitudinais. Os resultados indicam que a dinâmica flexural exibe maior sensibilidade à detecção de danos, principalmente devido à maior amplitude e densidade dos picos em toda a faixa de frequência investigada. Este estudo fornece uma compreensão mais profunda da capacidade da técnica de detectar danos em cenários mais complexos e amplia as aplicações do modelo.
Influência de danos e periodicidade estrutural na impedância eletromecânica aplicada a SHM
Keywords: Structural health monitoring; Electromechanical impedance; Analytical model; Damage; Periodic structures